Pendekatan Special Perkebunan Kelapa Sawit terhadap Daya Dukung Lingkungan di Kecamatan Anggaberi Kabupaten Konawe - Mukaddas, Jamal; Taufik, Taufik (Jurnal Ilmiah Dikdaya, 2022)
The objectives of this study were (1) to identify the existing conditions of oil palm plantations in Anggaberi District, Konawe Regency (2) to analyze the condition of the carrying capacity of the environment in Anggaberi District, Konawe Regency (3) to formulate the concept of controlling environmental carrying capacity in Anggaberi District, Konawe Regency . This research was carried out through the stages of research methods including conducting studies on primary data and secondary data, namely the availability of geospatial information on the research area, D3TLH information, in the formulation of the concept of carrying capacity control. Based on the results of spatial identification, it shows that there are 2 villages and 1 sub-district that are the location for developing oil palm plantations in Anggaberi District, namely Andabia Village, Lerehoma Village, Wunduongohi Village, with a total area of 2500 Ha. The results of the analysis of environmental service index performance in Anggaberi District are divided into 5 (five) index classes, namely very low class, low, medium, high and very high class. The average carrying capacity index value of the provision, regulation and support ecosystem services in Konawe Regency, where the provision of environmental services ranges from 2.38 to 3.44 (low - high class), the regulatory environmental service index is in the range of 2.12 to 3.18 (low to medium class) and supporting environmental services index values ranging from 2.55 to 2.95 (low to medium class). In detail, the distribution of the index of carrying capacity for environmental services provision, regulation and support in Anggaberi District. The carrying capacity and carrying capacity of the region are highly dependent on the ability of the ecosystem to produce provision, maintenance and protection services. The ability of ecosystems to produce the services mentioned above is very dependent on the condition/state of the landscape or ecoregion conditions, the condition of the distribution of natural vegetation and the condition of land cover throughout the mainland of Konawe Regency. The combination of these three variables greatly determines the ability of ecosystems to produce services, both provisioning services, regulatory services and protection services.